Ekonomi Masyarakat Indonesia Setelah Pandemi Covid-19 - Devika Amelia Nurjanah; Nilam Dwi Apriliyani; Fradinda Amelia Hapipah; Choirunnisah Choirunnisah; Firdha Anissa (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
The Covid 19 pandemic has caused paralysis in various sectors of life throughout the world, from social, political, economic to cultural. The thing that really has an impact is the economic sector where there are many restrictions in daily activities that cause a decrease in people’s purchasing power. This research aims to find out the condition of Indonesia economi after Covid-19 pandemic based on literature study. In this study using the research method of literature study, namely the activities of collecting literature, reading and recording and processing into research material. In this study also used a qualitative approach, namely research procedures in the form of descriptive data from spoken or written words or from the form of policy actions. In this study, data collection and analysis activities were carried out to develop a substantive theory based on empirical data. Based on the results of this study, it can be concluded that the economy of the Indonesian people after the Covid 19 pandemic did not experience a recession and continued to grow at a significant rate.